What kind of mother eaudiobook A novel. - Chapman, Clay (Blackstone Publishing, 2023)
Nicholas Sparks meets The Empty Man in this modern Southern Gothic horror about a palm reader swept up in a disturbing missing-child case with a twist you won't see coming. After striking out on her own as a teen mom, Madi Price is forced to return to her hometown of Brandywine, Virginia, with her seventeen-year-old daughter. With nothing to her name, she scrapes together a living as a palm reader at the local farmers market. It's there that she connects with old high school flame Henry McCabe, now a reclusive local fisherman whose infant son, Skyler, went missing five years ago. Everyone in town is sure Skyler is dead, but when Madi reads Henry's palm, she's haunted by strange and disturbing visions that suggest otherwise. As she follows the thread of these visions, Madi discovers a terrifying nightmare waiting at the center of the labyrinth—and it's coming for everyone she holds dear. Combining supernatural horror with domestic suspense into a visceral exploration of parental grief, What Kind of Mother cements Clay McLeod Chapman's reputation as a "star" (Vulture) and "the twenty-first century's Richard Matheson" (Richard Chizmar, Chasing the Boogeyman).